Spaces for Jihād: Indian Muslims and Conceptions of Citizenship - Abdelhalim, Julten (2013)
This thesis deals with the question of how Indian Muslims make use of the spaces and channels granted by the democratic framework to accommodate their Islamic identity with the secular one, and to what extent their Islamic identity is conceived (or perceived) as either conducive or conflicting with the political setting they live in. By comparing between a majority and minority setting, an analysis of how the socio-political context shapes citizens’ perceptions of multiple variables such as their sense of political efficacy, agency, conception of citizenship rights and belief in democracy is undertaken.
Keywords: Hochschulschrift; Bürger; Muslim; Indien